Ceramics from the Tanjung Simpang Mengayau shipwreck: Classification and description - Masyella Masbaka; Soon, Stephen Chia Ming; Baszley Bee Basrah Bee (SEAMEO SPAFA, 2025)
The Tanjung Simpang Mengayau shipwreck ceramics, from Kudat, Sabah, have previously been identified as Chinese ceramics dating to the Northern Song Dynasty (960-112 CE) by Sjostrand (2003). In this study, the shipwreck ceramic samples can be classified into 11 main ceramic types based on form, i.e., shape, function, glaze colour and decoration. The ceramic types are bowls, jars, plates, ewers, kendis, bottles, covered boxes, basins, teapots, vases and lids. The majority of ceramics are bowls with olive green glaze, followed by jars with various shades of brown glazes, and ewers with white glaze. These ceramics are mostly decorated with bamboo-comb incision, such as vertical lines on the outer body for bowls and plates, whereas jars and jarlets are predominantly decorated with floral or pattern incisions. The inner body of most of the bowls, plates and basins have either floral or pattern incisions or they have no decoration at all, while teapots and ewers are usually undecorated. These ceramics were part of the cargo of a ship travelling from China, via the Philippines, to Borneo. It is believed to be the oldest cargo ship so far found in Malaysian waters, providing important evidence of early maritime trade from China to Borneo, as well as cultural affinities between Tanjung Simpang Mengayau and other areas of the Indonesian archipelago.